Industrial relations and working conditions developments in Europe 2012 - Curtarelli, Maurizio; Fric, Karel; Galli da Bino, Camilla; Aumayr, Christine; Cabrita, Jorge; Kerckhofs, Peter; Preller, Joeran (Dublin, 2013)
"This annual review describes the main developments in industrial relations and working conditions in 2012 in the former 27 EU Member States and in Croatia and Norway, at both national and EU level. The report first sketches the current economic situation in these 29 countries, pointing to relevant political and legislative developments in individual countries. It discusses trends in industrial relations, including changes in the role and organisation of the social partners and the impact of government measures and legislation. The report highlights policies and initiatives, legislative developments and collective bargaining landmarks in five areas – employment conditions, wages, health and safety, skills and competencies, and working time – from the dual perspective of working conditions and industrial relations developments.